The Fekete–Szegö functional associated with $m$-th root transformation using conical domains - Gurusamy, P.; Çağlar, M.; Sivasubramanian, S.; Cotirla, L. I. (Ukrains’kyi Matematychnyi Zhurnal, 2024)
UDC 517.5Let $\mathcal{A}$ be the class of analytic functions in the open unit disk  $\mathbb{U}=\{z\in \mathbb{C}\colon |z|